The HRM Tango Impact of Availability and Use of Flexibility HR Practices on Organizational Performance - Mobarez, Ayman (The Arab Journal of Administration, 2018)
This research investigated the effects of flexibility HRM on employee outcomes over time, as well as the role of age in these relations. Based on work adjustment theory, it was predicted that availability and use of flexibility HRM would be positively related to employee engagement, as well as higher job performance. Moreover, the researcher postulated different hypotheses regarding the role of employee age. While generation theory predicts that younger generations would react more strongly to flexibility HRM in relation to engagement, SOC-theory of aging predicts that older workers respond more strongly in relation to job performance. Moreover, the researcher found partial support for the moderating role of age in the relations of flexibility HRM with the outcomes: Flexibility HRM was important for younger workers to enhance engagement, while for older workers it enhanced their job performance. The research shows that the effectiveness of flexibility HRM depends upon employee age and the type of outcome involved, and consequently theory on flexibility at work should take the age of employees into account.